2020
DOI: 10.2298/sarh190109129d
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and factors associated with cervical cancer screening among women in the general population: Evidence from National Health Survey

Abstract: Introduction/Objective Serbia has been burdened with one of the highest cervical cancer incidence and mortality rates in Europe. The objective of the study was to estimate the prevalence and factors associated with compliance to cervical cancer screening among women in the general population. Methods The study used the data from 2013 National Health Survey of the population of Serbia. Logistic regression analysis was further used to examine demographic and socioeconomic factors which affect the disparities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…Previous cost-effectiveness studies have shown that shifting to a combination of spaced HPV screening program along with an HPV vaccination campaign will be cost effective in reducing cervical cancer mortality. 5 Similar to other studies from Lebanon and from other low-and middle income and high-income countries, [6][7][8][9] our pilot study shows that participation in a screening program is affected by the socioeconomic status, the education level, awareness, the income, and place of residence, as well as the interaction with healthcare providers, especially doctors. Moreover, the absence of adequate national joint Health Information System (HIS)…”
Section: Discussionsupporting
confidence: 84%
“…Previous cost-effectiveness studies have shown that shifting to a combination of spaced HPV screening program along with an HPV vaccination campaign will be cost effective in reducing cervical cancer mortality. 5 Similar to other studies from Lebanon and from other low-and middle income and high-income countries, [6][7][8][9] our pilot study shows that participation in a screening program is affected by the socioeconomic status, the education level, awareness, the income, and place of residence, as well as the interaction with healthcare providers, especially doctors. Moreover, the absence of adequate national joint Health Information System (HIS)…”
Section: Discussionsupporting
confidence: 84%
“…The highest percentage of respondents did their PAP-tests after they were recommended by doctors (52.3%); 45% of women did it on their own initiative, and only 2.7% did it after they had been summoned to participate in an organized screening by their doctor. The most important factors in women who had never undergone PAP-tests were the following: age (being within the youngest or the oldest age group), rural residence and low level of education, poor socio-economic status, and marital status (have never married) ( 43 ).…”
Section: Discussionmentioning
confidence: 99%